A predictive study of students’ social presence and their interconnectivities in the social network interaction of online discussion board (Journal of Applied Learning and Teaching, 2022)
Effective online interaction is beyond interacting with whomever. The quality of social interconnectivity matters. Social presence plays a vital role in building an effective online learning community. This study empirically examined: how online social presence will predict various aspects of students’ social interconnectivities (i.e., in-degree, out-degree, betweenness centrality, closeness centrality, eigenvector centrality, reciprocated vertex pair ratio, & PageRank) in the social network of discussion board within an online course? The predictive utility of social presence for all social network interconnectivity was supported, but reciprocated vertex pair ratio, so-called two-way interconnectivity was not. Social presence serves as a strong predictor for social interaction and interconnectivity. Learners with higher social presence are more likely to play distinguished roles of influencer, liaison, transmitter, social strategist, and prestigious figure of a community of learners. The findings would support online instructors to facilitate, guide, and support their students to navigate through the convoluted social interconnectivity effectively and continuously.